Mapping Grizzly Bear Habitats for Conservation Planning in the Central Interior of British Columbia - Nielsen, Scott (Canadian Institute for Studies in Publishing Press, 2011)
The Central Interior and Sub-Boreal Interior ecoprovinces of British Columbia represent an important transitional population of grizzly bears (Ursus arctos L.) occupying the area between two major mountain systems (Coastal Ranges and Central Rockies), as well as defining the boundary of extirpated range in the Fraser Plateau South. To assist ecoregional planning in the area, grizzly bear habitat models were produced for density, mortality risk, and source-sink habitat. Bear density was based on population estimates for each management unit and downscaling approaches using local habitat suitability rankings; mortality risk was modelled using 339 mortality locations from 2004 to 2007 and a suite of environmental and anthropogenic factors as predictors. Both models were combined to form a two-dimensional framework of habitat states representing source-like and sink-like habitats that help prioritize areas for protection and restoration (road decommissioning), respectively, as well as provide a basis for comparing with other biodiversity features. Irreplaceability values based on rare biota and unique habitats measured as the sum of runs in Marxan were significantly higher in grizzly bear source habitats than sink habitats suggesting that protection of grizzly bear source habitats would confer an umbrella or surrogate effect to other biodiversity.